Keterlaksanaan Penilaian Autentik Dilihat dari Pengalaman Mengajar dan Kualifikasi Pendidik (UPEJ Unnes Physics Education Journal, 2019)
This study aims to determine the level of authentic assessment of the physics learning of high school in Purbalingga Regency in terms of perception, planning, implementation and reporting aspects, then its relationship to teaching experience, education level, and teacher gender, as well as the tendency of the national exam results of the last 3 years. The type of research using descriptive qualitative. The research subject was a high school physics teacher in Purbalingga District consisting of 8 respondents. Sampling uses purpose sampling techniques from 11 schools that have implemented the 2013 curriculum. The main data sources are obtained from exclusive interviews with respondents and supported by document review and learning observation data from each respondent. The results of the analysis showed that the implementation of authentic assessment in high school physics learning in Purbalingga Regency was in good category, the teaching experience of physics teachers has no effect on the implementation of authentic assessments, physics teachers with an S2 level of education are able to carry out authentic assessments better, male physics teachers are able to carry out authentic assessments better, and there is no effect on the implementation of authentic assessments of the results of national examinations